2009
DOI: 10.1002/eco.38
|View full text |Cite
|
Sign up to set email alerts
|

Linking water sources with foliar nutrient status in upland plant communities in the Everglades National Park, USA

Abstract: Plant communities within an ecosystem can vary in water source usage and nutrient availabilities, thus permitting community coexistence and diversity. We investigated the differences in water source utilization in two ecologically important upland plant communities: tropical hardwood hammocks and pine rocklands in the predominantly flooded Everglades ecosystem. We then linked these differences with their foliar nutrient levels and photosynthetic performance as measured by υ 13 C abundance. Based on a compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 49 publications
7
40
0
Order By: Relevance
“…18 O values in topsoil than ground water have also been observed by Saha et al (2009) in similar environmental conditions in Miami, associated with water condensation occurring at night in the upper soil layers. Condensation has been shown to deplete d…”
Section: Recorded Dmentioning
confidence: 56%
“…18 O values in topsoil than ground water have also been observed by Saha et al (2009) in similar environmental conditions in Miami, associated with water condensation occurring at night in the upper soil layers. Condensation has been shown to deplete d…”
Section: Recorded Dmentioning
confidence: 56%
“…The upper layer of oolitic rock is resistant to mixing of fresh and salt water so that the lens of fresh groundwater is maintained even near the edge of the sea. Skeletal, organic soils of 10 cm or less provide little rooting space in these rocklands (Ross et al 2003), though the pine trees have some ability to access the freshwater lens through limestone bedrock (Saha et al 2009). …”
Section: Introductionmentioning
confidence: 98%
“…In both species, leaf N:P ratio was > 16 in Control trees which gives an indication of P limitation on the islands. Similarly, Saha et al (2009) also reported high mean leaf N:P ratio for hammock (45) and pineland (42) species in the Everglades. Richardson et al, (1999) also reported leaf N: P ratios of 70-84 in sawgrass (Cladium jamaicense) from Everglades prairies.…”
Section: Critical N:p Ratio and Nutrient Limitationmentioning
confidence: 81%